Identification of Chemical Constituents of Oroxylum Indicum (Bonglai) Hydrosol (Remaining Water After Oil Distillation) Extracted By Hydrodistillation Method - Nur Ain Qaisarah, Azhar; Mohd Aizudin, Abd Aziz; Muhammad Auni, Hairunnaja; Norasiha, Hamid (UCYP Press, 2022)
Oroxylum Indicum (Indian Trumpet Flower) or called Bonglai in Malay is a medicinal plant widely used, especially in the Indian medicine system. Oroxylum Indicum can be extracted by the hydrodistillation method to obtain the essential oil and hydrosol. Nevertheless, the chemical constituents of the hydrosol of the leaves are yet to be determined as hydrosol is always discarded, leading to the wastage of products. Thus, this study investigated the chemical constituents of Oroxylum Indicum leaves hydrosol extracted by hydrodistillation by varying temperatures and determined the functional groups of the active constituents in the leaves for the benefit and usage in pharmaceutical industries. Hydro distillation is carried out at different temperatures to study the effect of temperatures on the active compounds in the hydrosol. The hydrosol sample of the leaves will be extracted by hydrodistillation method at temperatures of 50℃, 70℃ and 80℃ and separated via rotary evaporator, and later analyzed by GC-MS and FTIR analysis. This study will help us to identify the value and amount yield of the chemical constituents of Oroxylum Indicum leaves hydrosol which will be able to determine whether it will have significant values equal to the essential oil. From FTIR analysis, the functional groups for all samples are the same which are O-H stretch, H- bonded, N-H stretch and C=C stretch. The chemical constituents of Oroxylum Indicum hydrosol were determined by GC-MS analysis. The major components of hydrosol produced at 50℃ are squalene (10.44%), 2ethylehexyl palmitate (8.56%), palmitic acid (7.50%), and di-n-2-propyl pentyl phthalate (1.69%), and at 70℃ is acetic acid (5.88%) only, while at 80℃ are only traces components respectively. This is due to most compounds contained may be decomposed during the preparation of samples prior to both analyses also the efficiency of the system and procedure during the extraction.